1997
DOI: 10.1007/s001250050851
|View full text |Cite
|
Sign up to set email alerts
|

Time and frequency domain estimates of spontaneous baroreflex sensitivity provide early detection of autonomic dysfunction in diabetes mellitus

Abstract: Diabetic autonomic dysfunction, even when not yet manifest, is associated with a high risk of mortality [1±11] which makes its early identification clinically important. In the early eighties Ewing and co-workers [1,12] validated a battery of laboratory tests for identification of autonomic abnormalities in patients with diabetes mellitus. These tests consist in the measurement of the heart rate changes induced by manouvers such as deep breathing, Valsalva and standing which engage reflexes that alter vagal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
147
2
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(167 citation statements)
references
References 36 publications
12
147
2
6
Order By: Relevance
“…Moreover, we also uncovered the large-scales MCAE between ECG R-R intervals and PPG pulse amplitudes of left index finger decreased in the same manner in type 2 diabetes [31]. Several studies have shown that as compared with those free of diabetes, diabetic patients with cardiac or peripheral autonomic neuropathy related to poor glycemic control and sedentary status have lower baroreflex sensitivity [32,33]. The impaired short-term cardiovascular control in diabetes mellitus may be caused by the functional or structural impairment of nerve fibers of the autonomic nervous system innervating the heart and blood vessels [34].…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, we also uncovered the large-scales MCAE between ECG R-R intervals and PPG pulse amplitudes of left index finger decreased in the same manner in type 2 diabetes [31]. Several studies have shown that as compared with those free of diabetes, diabetic patients with cardiac or peripheral autonomic neuropathy related to poor glycemic control and sedentary status have lower baroreflex sensitivity [32,33]. The impaired short-term cardiovascular control in diabetes mellitus may be caused by the functional or structural impairment of nerve fibers of the autonomic nervous system innervating the heart and blood vessels [34].…”
Section: Discussionsupporting
confidence: 54%
“…Essentially, these previous findings were replicated here by: (1) showing a lower global HRV (assessed by the SD of RR interval); (2) the relative increase in the lowfrequency components; (3) the relative and absolute reduction in the high-frequency components of HRV; and (4) the higher low-frequency:high-frequency ratio, as assessed by spectral analysis. It is of note that reduced BRS was found to be a sensitive marker of autonomic cardiovascular dysregulation in a population of type 1 diabetic patients with a wide range of age and diabetes duration [10] and that such a reduction in BRS has furthermore been repeatedly reported by different studies in type 1 and type 2 diabetic patients [9,11,12,15]. Our findings also support these previous data, but, importantly, do so even in the absence of clinical complications or in the absence of alterations in the autonomic function tests.…”
Section: Discussionmentioning
confidence: 76%
“…A high prevalence of CAN, reduced HRV and blunted spontaneous BRS in patients with type 1 as well as in patients with type 2 diabetes have been reported previously [9][10][11][12][13][14][15]. It is of note that the tests used allow early detection of abnormalities in the autonomic nervous system.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, heart-rate variability (HRV) and, more recently, the sensitivity of spontaneous baroreflex control of the heart rate (baroreflex sensitivity, BRS), have been used to assess autonomic dysfunction as well. It has been proposed that these measures might be even more sensitive than the Ewing battery [4,5,6,7].…”
mentioning
confidence: 99%
“…Autonomic function has been reported to decrease in relation to age [8,9,10,11,12,13] and to differ between men and women [9,14,15]. Furthermore, diabetic patients have lower values on the Ewing battery [3,16,17,18,19], of the spectral analysis of HRV [4,16,20,21], and have a low BRS [5,22] in comparison with normal glucose tolerant control subjects. Besides their application in the assessment of cardiovascular autonomic function in diabetic patients, HRV and BRS are used in cardiology for risk stratification after myocardial infarction.…”
mentioning
confidence: 99%